TRANSFORMASI WARISAN BUDAYA MENJADI WISATA EDUKASI: INISIATIF DEMONSTRASI PEMBUATAN BOKOR DI DESA BRESELA - Budiadnyani, Ni Putu; R. Aprilyani Dewi, Putu Pande; Indraswari, I Gusti Agung Ayu Pramita; Kusuma, Putu Sri Arta Jaya (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The transformation of cultural heritage into educational tourism presents a unique opportunity to not only preserve time-honored traditions but also stimulate local economies. This endeavor, however, demands nuanced strategies that carefully balance the need for authenticity with the imperative of accessibility. The "Bokor-Making Demonstration" initiative in Desa Bresela exemplifies such an effort, aiming to convert the traditional craft of bokor making into an engaging and immersive educational experience for visitors. This initiative holds promise for promoting a deeper cultural understanding and offering tangible economic benefits to the local community. Realizing this potential, however, requires meticulous planning and execution, ensuring that the educational component is both informative and respectful of the cultural heritage (Munjal, 2019). The demonstration must strive to foster a genuine appreciation for the craftsmanship and cultural significance of bokor-making, while also catering to the needs and interests of diverse visitors. This delicate balance is essential for creating a sustainable and mutually beneficial model of heritage tourism that enriches both the local community and the visiting public.